Impact of mindfulness-based tri-modal prehabilitation on functional recovery and selected surgical outcomes of patients with colorectal cancer admitted to surgical hospital wards: the first international randomised control trial for mindfulness-based tri-modal prehabilitation - Bawantha Gamage; Manori Nayanakantha Gamage; Nilushika Madushani Perera; Chadani Samararatna Kodikara; Jayamina Udhara Munasinghe Wijeratne; S M D P Seneviratne Alles; Thavendra Kumaran; J M Chandima Jeewandara; Sanath Thushara Chamakara Mahawithanage (BMJ Open)
Introduction Colorectal cancer (CRC) is the third most common and second most deadly cancer worldwide, with significant morbidity and mortality risks. Despite advancements in surgical care, postoperative complications and recovery challenges persist. The severity of these issues is linked to preoperative functional capacity and emotional distress. Mindfulness, known for enhancing emotional well-being, is being considered as a promising intervention in cancer care. This study investigates the effectiveness of mindfulness-based tri-modal prehabilitation in improving functional recovery and surgical outcomes for patients with CRC.Methods and analysis The sample size of this prospective, randomised controlled trial was calculated based on the primary outcome, which is the detection of the clinically significant difference in a 6 min walk test (6MWT). With our population variables, the size of the sample was estimated for an α level of 0·05 (two-sided) and 80% power to detect a clinically meaningful difference between groups at postsurgical follow-up of 32 m, with an estimated variability of 64 m based on previous studies. The final sample size is 72 patients, in both arms. Both groups will receive a 4-week standard tri-modal prehabilitation. The intervention group will receive a mindfulness practice module. Outcomes will be measured at four different time intervals for each patient. Secondary outcome measures cover nutritional status, psychological status and selected biomarker status. Patient recruitment to the study started in April 2022.Ethics and dissemination This study was approved by the Ethics Review Committee of the Faculty of the Medical Sciences University of Sri Jayewardenepura (Registration No: FMC/ USJP ERC 29/19) and the Ethics Review Committee of Colombo South Teaching Hospital (Reference number 915). The research results will be published in peer-reviewed publications and presented at international conferences.Trial registration number SLCTR/2020/022.